Predictive model for dysmenorrhea level in female Taekwondo athletes: Investigating the influence of BMI and micronutrient intake - Fitrianingsih, Asti Dewi Rahayu; Santanu, Ayu Mutiara; Novitasari, Putri (Journal Sport Area, 2023)
Disturbances during menstruation such as dysmenorrhea affect the performance of female athletes. However, research on the physiologic conditions of female Taekwondo athletes was still very limited. This study aimed to obtain a predictive model for the level of dysmenorrhea and to test which variable had the most influence on the rate of dysmenorrhea. The research design adopted cross-sectional methods. Multiple linear regression analysis was performed to analyze the effect of BMI and micronutrient intake of nine elite regional and national female Taekwondo. The results showed that the average female athlete had a normal BMI, while for micronutrient intake per day, the average intake of vitamin E was low, the vitamin B6 intake was low, Magnesium intake was low and Calcium intake was fulfilled. The most influence on the occurrence of primary dysmenorrhea in female Taekwondo athletes was calcium intake. This study was limited to measurements of BMI and dietary micronutrient intake, which might help provide data that coaches, athlete nutritionists, and athletes could be used to predict and assess the incidence of primary dysmenorrhea. More research could use the Food Frequency Questionnaire (FFQ), which could better explain how often athletes consumed certain food ingredients over a specific time period.